Revisión de Alcance de la Actividad Antibacteriana de Estructuras Organometálicas en Ensayos in vitro: Scoping Review of the Antibacterial Activity of Organometallic Frameworks in in vitro Assays - Ceceña Lara, Cesar Gustavo; Chapa González, Christian (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
In this scoping review, the PRISMA methodology was used and, after the inclusion and exclusion criteria used in a total of 700 documents, four documents were analyzed on the antibacterial activity of organometallic frameworks in vitro tests, the foregoing in order to determine the most suitable organometallic framework to inhibit bacteria due to the potential of said frameworks in the field. Using the Web of Science and ScienceDirect databases, a total of sixteen in vitro tests with different microorganisms and four different organometallic frameworks were compiled. After analyzing the inhibitions presented in each test, it was concluded that the best organometallic structure in terms of antibacterial activity in vitro tests, was the Cu-MOF-NPs framework; due to being the one that presented an inhibition area greater that the rest of the frameworks in additions to being the one that presented a greater quantity of tests with a greater quantity of microorganisms.